2019
DOI: 10.18438/eblip29564
|View full text |Cite
|
Sign up to set email alerts
|

Scale Evaluating the Information Literacy Self-Efficacy of Medical Students Created and Tested in a Six-Year Belgian Medical Program

Abstract: A Review of: De Meulemeester, A., Buysse, H., & Peleman, R. (2018). Development and validation of an Information Literacy Self-Efficacy Scale for medical students. Journal of Information Literacy, 12(1), 27-47. Retrieved from https://ojs.lboro.ac.uk/JIL/article/view/PRA-V12-I1-2 Abstract Objective – To create and validate a scale evaluating the information literacy (IL) self-efficacy beliefs of medical students. Design – Scale development. Setting – Large, public research univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In addition, the reliability of this scale (e.g., CR = 0.938 CA = 0.929) was also reported by Soroya et al [ 41 ] with medical students. Richardson [ 42 ] also reported its suitability with Belgian medical students as the values of CA were greater than 0.70 for overall scale and each of its sub-scales. The certain other studies also reported the reliability and validity of this scale with other students from varied disciplines, geographical and cultural contexts [ 43 , 44 ]…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the reliability of this scale (e.g., CR = 0.938 CA = 0.929) was also reported by Soroya et al [ 41 ] with medical students. Richardson [ 42 ] also reported its suitability with Belgian medical students as the values of CA were greater than 0.70 for overall scale and each of its sub-scales. The certain other studies also reported the reliability and validity of this scale with other students from varied disciplines, geographical and cultural contexts [ 43 , 44 ]…”
Section: Methodsmentioning
confidence: 99%